The relationship of macroeconomic variables and real estate distribution yield in Malaysia / Alyaa Farzana Shahril Azlan - Shahril Azlan, Alyaa Farzana (Faculty of Business Management, 2018)
Real Estate Investment Trusts (REITs) has already reached its twenty nine years in the stock market industry. As in 2018, eighteen companies were listed in the REITs market. Even though the market is well established, Malaysian investors seems to have less interest to invest in REITs. One of the main issues is lack of past information and research on the REITs in Malaysia especially when it relates to the macroeconomics variables. Thus, this study was conducted in order to investigate the relationship between macroeconomics variables and real estate distribution yield in Malaysia. The significance of this study are to give more exposure and interest to the Malaysian investors towards REITs. This study selected nine listed REITs companies in Bursa Malaysia from 2010 until 2017. Moreover, descriptive analysis and multiple linear regression analysis were used as method of the study. The findings of this study showed that inflation rate has the most significant relationship with distribution yield. Meanwhile, gross domestic product, interest rate, and KLCI index showed positively significant relationship.